Effect of Acid Value on TBHQ and BHT Losses in Heating Oils: Identification of the Esterification Products of TBHQ and Free Fatty Acids. (10th July 2014) - Li, Jun; Bi, Yanlan; Liu, Wei; Sun, Shangde; Liu, Cuifang; Ma, Sumin
Abstract: The loss of phenolic antioxidants is one of the major problems associated with the food frying process. As temperature increases and heating time is prolonged, losses of both tertiary butylhydroquinone (TBHQ) and butylated hydroxytoluene (BHT) are significantly increased. In this work, the effect of different types of free fatty acids (FFA) and the acid value (AV) of soybean oil (SBO) on TBHQ and BHT losses during heating were systematically studied. The results showed that the higher the AV of SBO at 120 or 180 °C, the greater the TBHQ loss. The type of FFA also had an observable effect on TBHQ losses at both temperatures, whereas FFA type had no effect on BHT losses. Employing high performance liquid chromatography and liquid chromatography–mass spectra (LC–MS analysis, it was determined that esterification of TBHQ with FFA (C8:0, C18:0, C18:1 ) occurred at 120 or 180 °C, whereas esterification of BHT with FFA (C8:0, C18:0, C18:1 ) in SBO was not observed. Nuclear magnetic resonance analysis showed that esterification occurred at the 4‐position of TBHQ.